Why Can't We All Just Get Along? The Conflict between School and Club Sports in the United States. Issue 1 (2nd January 2020) - Bennett, Gregg; Keiper, Paul; Dixon, Marlene
ABSTRACT: There has been growing discontent between American school-based sports programs and those offered by youth sports clubs. Both institutions offer numerous benefits while likewise facing systematic challenges. However, there is a paucity of research focused on the pronounced conflict between school- and club-based sports programs in the United States. This article explores the conflict from a descriptive perspective. Much of the discontent between club- and school-based sports programs is based upon points of conflict surrounding athlete participation and priority. To investigate this matter, this manuscript examines (a) the status of school-based and club sports in America; (b) benefits and challenges of club- and school-based sports; and (c) the sources of conflicts between school-based and club sports. To conclude, we briefly describe possible solutions to the aforementioned conflict and provide insight regarding potential directions for future research.